2017
DOI: 10.2174/1874091x01711010001
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Deprivation as Measured by the Index of Multiple Deprivation and Its Association with Low Sex Hormone Binding Globulin in Women

Abstract: Objective:Sex hormone binding globulin (SHBG) is a marker of insulin resistance. Given established links between BMI and socioeconomic disadvantage, we investigated how SHBG varies by index of multiple deprivation (IMD).Research Design and Methods:Using laboratory data from a Midlands UK population of mixed ethnicity, we examined the relation between blood concentrations of SHBG and IMD in 1160 women aged between 17 and 71 years. Women with a serum SHBG >250 nmol/L were excluded.Results:Mean age was 28.7 (95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Given the association between elevated BMI and lower SHBG with insulin resistance in both men and women and the relation between low SHBG and higher plasma glucose, our findings are further evidence for the link between socioeconomic disadvantage and future risk of impaired glucose regulation. Furthermore, they accord with our recent general population survey showing that that lower SHBG levels in women are associated with a higher level of socioeconomic disadvantage …”
Section: Take Away Messagesupporting
confidence: 91%
See 1 more Smart Citation
“…Given the association between elevated BMI and lower SHBG with insulin resistance in both men and women and the relation between low SHBG and higher plasma glucose, our findings are further evidence for the link between socioeconomic disadvantage and future risk of impaired glucose regulation. Furthermore, they accord with our recent general population survey showing that that lower SHBG levels in women are associated with a higher level of socioeconomic disadvantage …”
Section: Take Away Messagesupporting
confidence: 91%
“…Furthermore, they accord with our recent general population survey showing that that lower SHBG levels in women are associated with a higher level of socioeconomic disadvantage. 15 It is of note that Merkin et al 16 reported that women who experienced a more disadvantaged socioeconomic status in childhood were at increased risk of PCOS in adulthood.…”
Section: Take Away Messagementioning
confidence: 99%
“…High deprivation is most likely a surrogate for either one or more risk factors. It is established that rates of obesity and potentially of insulin resistance are higher in more socially disadvantaged individuals [16]. Low vitamin D could be a causative or a surrogate factor in COVID-19 infection.…”
Section: Resultsmentioning
confidence: 99%
“…High deprivation is most likely a surrogate for either one or more risk factors. It is established that the rates of obesity and potentially insulin resistance are higher in more socially disadvantaged individuals 21 . Low vitamin D could be a causative or a surrogate factor in COVID‐19 infection.…”
Section: Discussionmentioning
confidence: 99%